Uniform hyperscanning paradigm to study cooperation and competition - Pablo A. Nogueira-Islas; Paola V. Olguín-Rodríguez; Hugo Tlahuext-Aca; Markus F. Müller (MethodsX)
It is assumed that social interaction like cooperation or competition takes place via synchronized interbrain activity, measurable via hyperscanning experiments. However, interbrain synchronization might also be due to common external stimuli without any genuine inter-personal interaction. In addition, a consistent experimental paradigm is required to distinguish between different modalities such as cooperation or competition. To facilitate retrospective analysis, it would also be desirable for the task that the participants have to perform not to be divided into short time intervals, but to be continuous over a longer period of time. Here we present an experimental protocol that allows • The same paradigm for different modalities • Tasks demands a continuous interaction during a period of minutes • Contains two different control conditions to differentiate between inter-brain synchronization provoked by genuine interpersonal interactions and accidental synchronization via common external stimuli.